LuAG:Ce/CASN:Eu phosphor enhanced high-CRI R/G/B LD lighting fidelity. Issue 31 (19th July 2019) - Huang, Yu-Fang; Chi, Yu-Chieh; Cheng, Chih-Hsien; Tsai, Cheng-Ting; Wang, Wei-Chun; Huang, Ding-Wei; Chen, Li-Yin; Lin, Gong-Ru
Abstract : Phosphor thickness and R/B power were analyzed to optimize the cold-white-light CRI to 80.4 and white-light VLC to 10.4 Gbps. Abstract : By passing a collimated red/green/blue laser diode (R/G/B-LD) beam through a yellow-orange luminescent Lu3 Al5 O12 :Ce 3+ /CaAlSiN3 :Eu 2+ (LuAG:Ce/CASN:Eu) phosphor glass, divergent white light with a color rendering index (CRI) beyond 80 at a correlated color temperature (CCT) of 6500 K is obtained for visible light communication (VLC) beyond 10 Gbps. The CCT of white light is unique as it can be tuned by flexibly adjusting the R/G/B-LD power ratio. Thinning the LuAG:Ce/CASN:Eu phosphor glass to 0.8 mm greatly improves the transmission performance of the white light but inevitably degrades its CRI to 41.1 at a CCT of 6509 K. In contrast, a 1.0 mm thick phosphor effectively enlarges the CRI up to 80.4 at a CCT of 6560 K while reducing the red and blue power. The trade-off between the phosphor glass thickness and R/G/B-LD power is studied to optimize the cold-white-light CRI beyond 80 and the white-light VLC up to 10.4 Gbps.